2020
DOI: 10.1007/s42452-020-2022-y
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in surface sediments of Lake Naivasha, Kenya: spatial distribution, source identification and ecological risk assessment

Abstract: Heavy metals retained in sediments pose a threat to aquatic ecosystem and society. Knowledge of the status and sustainability of lake sediment in areas undergoing rapid economic development is scarce, and yet it is required in order to achieve the United Nations Sustainable Development goals. We investigated heavy metal concentration in Lake Naivasha sediments using enrichment factor, geoaccumulation index, pollution load index (PLI), risk index (RI) and multivariate statistics to determine metal accumulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The sediments near the inlets of the rivers have more clay than the rest of Lake Malawi due to the deposition of eroded material from agricultural fields [58,60]. Another tropical lake with a sandier bottom than Lake Tana is the 9 m deep and 160 km 2 large Lake Navashi in Kenya that has 33% clay, 40% silt, and 30% sand [61]. The inflow and outflow to this lake that is located in the Rift valley was mostly via the subsurface.…”
Section: Relationship With Lake Depthmentioning
confidence: 99%
“…The sediments near the inlets of the rivers have more clay than the rest of Lake Malawi due to the deposition of eroded material from agricultural fields [58,60]. Another tropical lake with a sandier bottom than Lake Tana is the 9 m deep and 160 km 2 large Lake Navashi in Kenya that has 33% clay, 40% silt, and 30% sand [61]. The inflow and outflow to this lake that is located in the Rift valley was mostly via the subsurface.…”
Section: Relationship With Lake Depthmentioning
confidence: 99%
“…In 1969, irrigated horticulture began and continued to expand until today, complemented by the installation of the Olkaria Geothermal Power Station in 1984 (e.g., Harper & Mavuti, 2004; Otiang’a‐Owiti & Oswe, 2007; Stoof‐Leichsenring et al, 2011). As a consequence of its heavy use, Lake Naivasha is beset by severe problems such as introduced alien species, declining fisheries, and lake‐level decline caused by water abstraction for agricultural use (Harper & Mavuti, 2004; Odongo et al, 2019; Olando et al, 2020). This situation also affects lake levels at Sonachi because of their hydrological connection.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, Cr, Cu, and Cd datasets include 2, 4, and 1 outlier, respectively. The analysis showed that Cr outliers occurred in Lakes Bierzwnik (5) and Piaseczno Duze (42), Cu in Lakes Dlugie Wigierskie (12), Kamienny Most (24), Lubosz Wielki (33), and Wielkie (70), and Cd in Lake Trzebun (65).…”
Section: Variability Of Hm Concentrations In Surface Sediments Of Lak...mentioning
confidence: 99%
“…Dominant sources of HMs differ at the continental scale. In Africa, the dominant source of HMs is bedrock weathering, in North America mining and industry, and in Asia and Europe domestic wastewaters 11 .According to the latest study results, sediments are dominated by elements primarily originating from anthropogenic sources [12][13][14] . Many studies show that industrial sources generally have the greatest impact on HMs pollution 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation